2021
DOI: 10.15240/tul/004/2021-2-001
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Performance of Czech and Finnish Manufacturing Enterprises and Their Position in the Eu

Abstract: The aim of this article is to assess the innovation performance of innovative small, medium-sized, and large enterprises operating in the manufacturing industry in two European countries – the Czech Republic (CR) and Finland, and to determine their position within the EU based on a comparison with average values of created Fictitious EU Country (FEUC). The FEUC includes the indicators and population of the EU member countries whose data were available. The performed analysis is based on the use of selected key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…With specific reference to the effects of ESIF depending on the size of enterprises and the role they play in the innovation projects financed, there is not abundant literature. Despite this, there are some studies conducted in recent years which are focused on the differences produced between firms according to their size, but aimed at not-Andalusian regions (Santamaría & Nieto, 2009;Silva & Carrizo, 2018;Blaschke, Demel & Kotorov, 2021). us, while some studies using the same methodology (Segarra-Blasco, 2018) or different (Benkovskis, Tkacevs & Yashiro, 2019) have found that companies´size is a key factor other authors (Sande & Vence, 2021) found that large enterprises (LEs) have absorbed part of the expected impact in SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With specific reference to the effects of ESIF depending on the size of enterprises and the role they play in the innovation projects financed, there is not abundant literature. Despite this, there are some studies conducted in recent years which are focused on the differences produced between firms according to their size, but aimed at not-Andalusian regions (Santamaría & Nieto, 2009;Silva & Carrizo, 2018;Blaschke, Demel & Kotorov, 2021). us, while some studies using the same methodology (Segarra-Blasco, 2018) or different (Benkovskis, Tkacevs & Yashiro, 2019) have found that companies´size is a key factor other authors (Sande & Vence, 2021) found that large enterprises (LEs) have absorbed part of the expected impact in SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors have addressed the role of innovations within the development process in many research papers (Blaschke et al, 2021a(Blaschke et al, , 2021bBlaschke & Demel, 2019). In this paper, the topic of innovations is placed in the still current issue of Covid-19.…”
mentioning
confidence: 99%